2022
DOI: 10.3389/fendo.2022.949003
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of endocrine-related adverse events associated with interferon

Abstract: ObjectivesTo perform a systematic review and meta-analysis of interferon and endocrine side effects, including their incidence, evaluation, and management.MethodsPubMed was searched through March 7th, 2021, by 2 authors independently (LH Wang and H Zhao). Early phase I/II, phase III experimental trials, prospective and retrospective observational studies were included. Stata 16.0 (StataCorp LLC, 16.0) was the main statistical software for meta-analysis. The weighted incidence and risk ratio were estimated for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 127 publications
1
0
0
Order By: Relevance
“…There is no clear consensus on whether MS treatment treatment butffects thyroid function and autoantibody levels, according to our results, it is worthy to note that the level of (FT4) significantly decreased while (TSH) increased in our patients after six months of receiving the treatment compared to baseline levels although it's still in the normal range, which was similar to A systematic review and meta-analysis of endocrine abnormalities associated with interferon therapy which found that the proportion of hypothyroidism was higher than that of hyperthyroidism (23,24), on the other hand, the anti-TPO and anti-TG have increased significantly in our patients after three months of receiving the treatment, but return to near its previous level after 6 months of therapy, which is consistent with the other studies that performed by (Monzani et al, 1999) (25) and (Caraccio et al, 2005) (26). This can be explained by the fact that interferon beta maintains the anti-inflammatory status of the immune system.…”
Section: Discussionsupporting
confidence: 87%
“…There is no clear consensus on whether MS treatment treatment butffects thyroid function and autoantibody levels, according to our results, it is worthy to note that the level of (FT4) significantly decreased while (TSH) increased in our patients after six months of receiving the treatment compared to baseline levels although it's still in the normal range, which was similar to A systematic review and meta-analysis of endocrine abnormalities associated with interferon therapy which found that the proportion of hypothyroidism was higher than that of hyperthyroidism (23,24), on the other hand, the anti-TPO and anti-TG have increased significantly in our patients after three months of receiving the treatment, but return to near its previous level after 6 months of therapy, which is consistent with the other studies that performed by (Monzani et al, 1999) (25) and (Caraccio et al, 2005) (26). This can be explained by the fact that interferon beta maintains the anti-inflammatory status of the immune system.…”
Section: Discussionsupporting
confidence: 87%